Comparison of the Effectiveness of Mindfulness-Based Stress Reduction Group Therapy With Acceptance and Commitment Therapy on Severity of Pain and Health-Related Quality of Life in Patients With Migraine - Haji Seyed Javadi, Tahereh; Aghareb Parast, Najmeh; Shahsavani, Sahar; Chehraghi, Mir Javad; Razavi, Leila; Rahmani, Soheila; Nejati, Somayeh (International Clinical Neuroscience Journal, 2019)
Objective: Considering the prevalence of migraine and its detrimental effects on functioning, physical health, and quality of life as well as its psychosocial and social risks, the purpose of this study was to compare the effectiveness of mindfulness-based stress reduction treatment with treatment based on acceptance and commitment on the severity of pain and health-related quality of life in migraine patients. Methodology: In this study, a semi-experimental design was used with pre-test, post-test, a three-month follow-up, and a control group. Using purposive sampling and considering the inclusion criteria, 45 patients with migraine diagnosis were selected from among those referring to the neurology department of Imam Hossein Hospital in Tehran. They were then randomly assigned to two experimental groups and a control group. The first experimental group received group therapy based on mindfulness (n = 15; 90-minute sessions), the second experimental group received acceptance and commitment based intervention (n = 15; 90-minute sessions), and the control group (n = 15) received no intervention. All subjects responded to pain intensity and health-related quality of life questionnaires before the intervention (pre-test), after the intervention (post-test), and 3 months after the intervention (follow-up). Collected data were analyzed by one-way ANOVA. Findings: The findings showed that mean scores for the two experimental groups were significantly different from the control group in the post-test and follow-up phases in terms of severity of pain and health-related quality of life, while the mean scores for the two experimental groups did not differ significantly. The results emphasize the importance of these interventions for chronic diseases and offer new horizons in clinical interventions. Conclusion: The results of this study showed that mindfulness-based stress reduction therapy and acceptance and commitment therapy can positively affect the severity of pain and health-related quality of life in migraine patients, and any of them can be used to improve the above-mentioned variables.